2013
DOI: 10.1371/journal.pone.0063447
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Spatial-Temporal Clusters of HFMD from 2007 to 2011 in Shandong Province, China

Abstract: BackgroundHand, foot, and mouth disease (HFMD) has caused major public health concerns worldwide, and has become one of the leading causes of children death. China is the most serious epidemic area with a total of 3,419,149 reported cases just from 2008 to 2010, and its different geographic areas might have different spatial epidemiology characteristics at different spatial-temporal scale levels. We conducted spatial and spatial-temporal epidemiology analysis to HFMD at county level in Shandong Province, China… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
84
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(106 citation statements)
references
References 29 publications
20
84
2
Order By: Relevance
“…We classified the children into two groups by age using 2 years old as cut-off point, as children younger than 2 years old could not walk independently (28). By occupation, the children were grouped into scattered children and schooling children, where the scattered children were the pre-school children who have not been to kindergarten or school (29). We tested the statistical significance of differences between the effect estimates of the strata divided by potential effect modifiers by calculating the 95% confidence interval as:(Q1-Q2)±1.96(SE1)2+(SE2)2 where Q 1 and Q 2 were the effect estimates for each stratum (such as male and female), and SE 1 and SE 2 were their corresponding standard errors (30).…”
Section: Methodsmentioning
confidence: 99%
“…We classified the children into two groups by age using 2 years old as cut-off point, as children younger than 2 years old could not walk independently (28). By occupation, the children were grouped into scattered children and schooling children, where the scattered children were the pre-school children who have not been to kindergarten or school (29). We tested the statistical significance of differences between the effect estimates of the strata divided by potential effect modifiers by calculating the 95% confidence interval as:(Q1-Q2)±1.96(SE1)2+(SE2)2 where Q 1 and Q 2 were the effect estimates for each stratum (such as male and female), and SE 1 and SE 2 were their corresponding standard errors (30).…”
Section: Methodsmentioning
confidence: 99%
“…However, no spatial clustering studies of the incidence of severe HFMD or the proportion of severe HFMD cases among total HFMD cases have been conducted. Several studies have reported spatial clustering of the incidence of general HFMD (7)(8)(9)(10)(11), although all previous studies of HFMD clusters used district-level incidence data, which might have masked the potential effect of local environment. Thus, we analyzed the incidence of severe HFMD and the proportion of severe HFMD among total HFMD cases at the township level, which facilitated evaluation of the link between severe HFMD and environment factors at a higher geographical resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Spatio-temporal analysis is increasingly used in epidemiological research based on specific or routinely collected data from different sources [19,20,21]. Therefore, a better understanding of the spatio-temporal distribution patterns of HFMD would help in identifying areas and populations at high risk and then formulating and implementing appropriate regional public health intervention strategies to prevent and control the outbreak [22]. …”
Section: Introductionmentioning
confidence: 99%